Interactions between root endophytic microorganisms and the reduced negative ion release capacity of Phalaenopsis aphrodite Rchb. f. under high temperature stress - Ye, Qi; Lv, Wenzhuo; Lu, Yin; Wei, Zili; Guo, Yunxin; Wang, Peijie; Sun, Bingru; Tong, Yumei; Xuan, Shenke; Lin, Wei; Guo, Lijin (Frontiers in Plant Science, 2024)
To investigate the impact of high temperature stress on plants' capacity to generate negative oxygen ions and to elucidate the microbial mechanism by which climate change influences plants' emission of negative oxygen ions. In this study, Phalaenopsis aphrodite Rchb. f. was selected as the research object. By artificially simulating the climate, the control group (CK) and the hightemperature stress group (HS) were set up in the experiment. The study found that compared with the control group, the ability of P.aphrodite to produce negative oxygen ions significantly decreased when exposed to high temperature stress. Meanwhile, under high temperature stress treatment, peroxidase content increased by 102%, and proline content significantly increased by 35%. In addition, redundancy analysis results indicated a significant correlation between the root endophytic microbial community of P.aphrodite and negative oxygen ions, as well as physiological indicators. Therefore, under high temperature stress, P.aphrodite may affect the regulation of physiological indicators by modifying the composition of root endophytic microbial communities, thereby influencing the ability to release negative oxygen ions.